Reinvestigation the thermal and electrical transport properties of Tl7Sb2 - Charoenphakdee, Anek; Harnwunggmoung, Adul; Seetawan, Tosawat; Rattanapun, Chesta; Amornkitbamrung, Vittaya; Kurosaki, Ken; Yamanaka, Shinsuke (My University, 2013)
The authors examined the thermal and electrical transport properties of Tl7Sb2 at temperatures ranging from room temperature to 400 K. The crystal system of Tl7Sb2 is cubic with the lattice parameter a = 1.16053 nm and the space group is Im3m. The polycrystalline samples were prepared by melting stoichiometric amounts of thallium and antimony. Although, usually the thermal conductivity of thallium compounds is very low (<1 Wm-1K-1), that of Tl7Sb2 was relatively high (~13 Wm-1K-1 at room temperature). This is because of the large electronic contribution to the thermal conductivity. © (2013) Trans Tech Publications, Switzerland.
Keywords: Electrical resistivity; Seebeck coefficient; Thermal conductivity; Tl7Sb2